Comparative study of colony hybridization with synthetic oligonucleotide probes and enzyme-linked immunosorbent assay for identification of enterotoxigenic Escherichia coli. - Sommerfelt, H (1988)
On the basis of the published nucleotide sequences of the genes that code for the heat-labile toxin LTh and the heat-stable toxins STaI and STaII of human enterotoxigenic Escherichia coli, a 34-mer and two 33-mer oligonucleotide probes were synthesized. To compare their relative efficacies in the detection and differentiation of enterotoxigenic E. coli, a colony hybridization technique using these probes and a GM1 ganglioside enzyme-linked immunosorbent assay using monoclonal anti-LT and anti-ST antibodies were used with 76 strains of E. coli with known enterotoxin profiles. For further evaluation of probe specificity, the enterotoxigenic bacteria Vibrio cholerae O1 and non-O1 and Yersinia enterocolitica were examined with the colony hybridization technique. The sensitivity of colony hybridization compared favorably with that of GM1 ganglioside enzyme-linked immunosorbent assay, and the two assays showed a high level of concordance in specific detection and differentiation of E. coli with various enterotoxin profiles (kappa = 0.906, P less than 0.00001). The probes did not hybridize with DNAs from strains of V. cholerae O1 or non-O1 or Y. enterocolitica.